PENGARUH PAJAK BPHTB DAN RETRIBUSI PARKIR TEPI JALAN UMUM TERHADAP PENDAPATAN ASLI DAERAH KOTA BATAM - Meliyana, Nurul; Effendi, Syahril (EDUTECH CONSULTANT, 2020)
This study aims to examine the effects of BPHTB tax and parking fees on the regional revenue. This research uses quantative method. The data taken from annual reports of target and realization of revenue from local taxes and regional levies from 2012-2018. Using mulple linear regression statistical analysis. Data are processed using Eviews 10 aplication. The results obtained that BPHTB tax has a significant effect to Regional Revenue of Batam City, indicated by probability value in the t-statistic test showing a value of 0,0000 where the value is smaller than significance value of 0,05. Parking levies do not have a significant effect on the Regional Revenue of Batam City , the calculation results obtained from the t-statistic test show value 0,8100 is greater than 0,05. F test results show a probability number of 0,000118<0,05, it is concluded that simultaneous BPHTB taxes and parking levies have a positive effects on the Regional Revenue of Batam City.